SOBRE EL SIGNIFICADO DE YUPANQUI EN REFERENCIA AL TÍTULO DE LOS ANCESTROS REALES DE LOS INKA - Arana Bustamante, Luis (2017)
From the information of Gonzáles Holguín’s classic colonial Quechua dictionary [1608] and from the perspective of ethnohistory and modern anthropology of social Inka organization I study here the significance of a Quechua word which is the key in the comprehension of the system of royal titles of ancestors of the Inka kings. I also made a suggestion about the connected term of yupana, usually attributed to tridimensional tablets of game in wood or stone frecuently collected in archaeological Andean museums.